Mapping, Planning, and Sample Detection Strategies for Autonomous Exploration. Issue 1 (3rd December 2013) - Das, Arun; Diu, Michael; Mathew, Neil; Scharfenberger, Christian; Servos, James; Wong, Andy; Zelek, John S.; Clausi, David A.; Waslander, Steven L.; Van, Michel; Wettergreen, David
Abstract This paper presents algorithmic advances and field trial results for autonomous exploration and proposes a solution to perform simultaneous localization and mapping (SLAM), complete coverage, and object detection without relying on GPS or magnetometer data. We demonstrate an integrated approach to the exploration problem, and we make specific contributions in terms of mapping, planning, and sample detection strategies that run in real‐time on our custom platform. Field tests demonstrate reliable performance for each of these three main components of the system individually, and high‐fidelity simulation based on recorded data playback demonstrates the viability of the complete solution as applied to the 2013 NASA Sample Return Robot Challenge.